BaO nanoparticle contribution to PVA on the way to become a more functional material - Beyazay, Emre; Sahin, Nazlican; Karabul, Yasar; Kilic, Mehmet; Ozdemir, Zeynep Guven (WILEY, 2023)
In this study, it is aimed to produce a non-carcinogenic and environmentally friendly biodegradable multi-functional PVA-based nanocomposite by improving its electrical properties and mechanical strength. For this purpose, BaO nanoparticles produced by the co-precipitation method, have been added to the PVA matrix between 0.5% and 5% by mass, and thick film nanocomposites have been produced. The structural properties of the samples and the doping particle have been investigated by FTIR, SEM, and XRD. While electrical measurements have been carried out by an impedance analyzer at room temperature between 20 Hz and 15 MHz frequency, tensile tests have been performed by a mechanical tensile device. The addition of 5% BaO nanoparticles not only increased the energy storage capability of PVA significantly (117%) but also managed to reduce the loss factor considerably (77%). Moreover, compared to other samples, PVA/5% BaO nanocomposite also stands out with its higher ac conductivity within the mid-and high-frequency range. Furthermore, the 5% BaO nanoparticle additive provided a serious benefit to the mechanical strength of PVA by improving its Young's modulus, toughness, and stress at the break at different rates. As a result, the BaO nanoparticle additive makes PVA a more functional material as well as more technologically desired.
Keywords: dielectric properties; loss tangent; mechanical durability; PVA; Young modulus; POLYVINYL-ALCOHOL; DIELECTRIC-RELAXATION; NANOCOMPOSITES; CONDUCTIVITY; PERFORMANCE; COMPOSITE; Polymer Science